Assessing Water Quality of Mamasın Dam, Turkey: Using Water Quality Index Method, Ecological and Health Risk Assessments. Issue 12 (26th November 2019) - Baştürk, Emine
Abstract: The water quality of Mamasın Dam, the drinking water source for Aksaray in Turkey, is investigated for assessment of ecological and health risks according to data between December 2015 and November 2016. Water quality index, ecological risk, and health risk assessments are determined to depend on the intensity of occurrence of parameters and seasonal and spatial distributions at different depth ranges. As a result, some ions such as Al, As, B, Ba, Co, F, Mn, Ni, Pb, Se, and Zn were found to be exceeding the limit values of the national regulatory standards. Besides, Pb is listed in Priority Substances and Certain Other Pollutants according to Annex II. Because the WQI values of the water quality are low (below 60), the source is suitable for industrial and agricultural usage; however, it cannot be used for drinking water supply without treatment. The trace element levels, especially Ag, Ba, Cu, Cr, and Zn, are potential pollutants for organisms. The non‐carcinogenic health risks of As threaten both adults and children at "medium" and "high" levels through oral ingestion. The B, F, and Pb elements have Hazard Index values above 0.1 and may cause a "low" level risk chronic disease for children by oral ingestion. Abstract : The water quality for different purposes is evaluated using the D‐water quality index (WQI) method. The resource is suitable for industrial and agricultural usage; however, it cannot be used for drinking water supply without treatment according to the D‐WQI. Arsenic is the most important pollutant for noncarcinogenic risks.